Collaboration entre chercheurs et praticiens dans le cadre du projet Saines habitudes de vie – éducation physique et à la santé - Cecília Borges; Enrique García Bengoechea; Shirley Gray; Paula Bush; Suzanne Guay; Alain Lefebvre; Katherine Baker et Sandy Farr; Thierry Mélinge; Margaret Amos; Anne Sophie-Aubin et Joli-Anne Mercier (Éducation et Socialisation)
Collaboration between researchers and practitioners has become more and more requested with regard to teacher professional development. Action-research presents itself as a way to implement devices of support aimed at establishing communities of practices (Savoie-Zajc, 2010). This article addresses some issues emerging from the collaboration between researchers and practitioners within the framework of a Healthy Lifstyles Promotion- Physical Education and Health project aimed at the consolidation of the role of physical educators as promoters of a healthy active lifestyles towards their students. We present the main themes and findings of this project inspired by continuum training, action-research and collaboration, that involved both beginner and experienced teacher participants from one French and one English School Board on the island of Montreal.Based on data stemming from the evaluation of eight workshops involving twelve teachers, we present four fundamentals pillars of this project : the respective role of the practitioners and the researchers, their collaboration, the knowledge that they constructed together and the temporality in this process.